2009
DOI: 10.1007/s11273-009-9155-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth and allocation by a keystone wetland plant, Panicum hemitomon, and implications for managing and rehabilitating coastal freshwater marshes, Louisiana, USA

Abstract: This paper attempts to establish linkages between growth by a keystone wetland plant, Panicum hemitomon Schultes, and the independent and interactive effect of nutrient and hydrologic regime to inform management and rehabilitation of thick-mat floating marsh (TMFM). To do so a manipulative glasshouse experiment employing created TMFM similar to that under consideration for field trials and two levels each of N, P and hydrology was conducted. P. hemitomon grew vigorously under saturated (flooding level with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The larger roots act as metal tie-rods in the ecological cement to give structural strength to the organic whole. We agree with Mayence and Hester (2010) who suggested that ''Quantifying the relationship between root length, diameter and tensile strength would benefit our understanding of the interaction between nutrient level and mat strength and is therefore warranted.'' and have work underway to investigate this aspect further.…”
Section: Discussionsupporting
confidence: 84%
“…The larger roots act as metal tie-rods in the ecological cement to give structural strength to the organic whole. We agree with Mayence and Hester (2010) who suggested that ''Quantifying the relationship between root length, diameter and tensile strength would benefit our understanding of the interaction between nutrient level and mat strength and is therefore warranted.'' and have work underway to investigate this aspect further.…”
Section: Discussionsupporting
confidence: 84%
“…Greenhouse experiments, for example, document how flooding is required for vigorous root and rhizome production in P. hemitomon (Mayence and Hester, 2010). The results from these same greenhouse experiments also suggest that the % N and % P in plant tissue increases with higher nutrient loading, which, however, also leads to insignificant or negative effects on root diameter, specific gravity or volume after 3 months (Mayence and Hester, 2010).…”
Section: Methodsmentioning
confidence: 94%
“…5. Nutrient enrichments of P. hemitomon mesocosms (Mayence and Hester, 2010) demonstrate that the % N and % P content in P. hemitomon tissue will rise with eutrophication. That outcome will result in a change in litter quality -the % N will be higher -and decomposition rates will rise as a result.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations